Doping effect on bandgap energy and luminescence spectrum for AlN-based semiconductor - Faris Azim Ahmad Fajri, Faris Azim; Hairol Aman, Mohammad Amirul; Ahmad Noorden, Ahmad Fakhrurrazi; Abdul Hamid, Ahmad Noor; Abdul Aziz, Azni (Springer Science and Business Media Deutschland GmbH, 2022)
This ongoing work reports the heavy doping effect on the Aluminum Nitride (AlN) semiconductor (SC) material, illustrated via its energy-band structure (EBS). The research correlates the bandgap energy (BE) and depletion region (DR), which are then applied to the estimation of light-emitting diode (LED) luminescence spectrum (LS). The measurements are compared with different dopant concentrations (1 × 1018 cm−3 –1 × 1021 cm−3). Having the Gallium Arsenide (GaAs) properties as the controlled variable, the EBS is validated with literature findings. The measured band gap energy of AlN shifts from 6.2435 to 6.2326 eV. It decreased as the dopant concentration increased. However, the active spatial regions, reduced from (1.0250 × 10−1 to 4.5000 × 10−3 µm) × 1 µm2. The findings are compared with the output LS of LED using the same SC material. The changes in BE and DR are consistent with the LS peak intensity wavelength and relative intensity to all the chosen doping concentrations. Though acquiring this consistency, an extensive discussion with collaboration in material science studies will further strengthen the understanding regarding these behaviours.